From The History of Traditional Methods of Water Use and Its Management System Among Uzbeks In The Late 19th – Second Half of The 20th Century - F. Sh. Rakhmonov (Pubmedia Social Sciences and Humanities, 2025)
The article, based on available sources and historical literature, describes the history of traditional methods of water use and water resource management systems among the Uzbeks in the late XIX – second half of the XX centuries. Special attention is given to the functioning of traditional irrigation networks, the role of community leaders in regulating water use, and the adaptation of these practices to changing political, economic, and environmental conditions. The study highlights the continuity of indigenous knowledge and its influence on modern approaches to water management in Uzbekistan